PERCEPTIONS OF SOCIAL NETWORKS BY ADULTS WHO ARE DEAFBLIND. - ARNDT, KATRINA; PARKER, AMY (American Annals of the Deaf)
FINDINGS ARE PRESENTED from a descriptive qualitative study of 10 adults who were deafblind who were interviewed about their social lives. Additional data were collected from a discussion board and e-mails from the study participants. Three findings emerged from the data: (a) Navigating adaptations was a significant part of socialization. (b) Gaps existed in work, family, and formal support networks. (c) The participants drew upon resiliency and advocacy to manage these gaps.